1999
DOI: 10.1108/02652329910305670
|View full text |Cite
|
Sign up to set email alerts
|

External information search for banking services

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…Many benefits such as customer service, competitive advantage, lower costs, functionality, multi-country needs, scalability, expanded capacity, and facilitating operational change can form the perception of the customer towards the services or products offered. However, Heaney and Goldsmith (1999) found that there is a positive relationship between perceived benefit and information search for banking services. This is so since the consumers search for more information when they perceive the benefits that can be obtained from the offered services.…”
Section: Service Quality and Perceived Benefit With Smes Owners' Satimentioning
confidence: 94%
See 1 more Smart Citation
“…Many benefits such as customer service, competitive advantage, lower costs, functionality, multi-country needs, scalability, expanded capacity, and facilitating operational change can form the perception of the customer towards the services or products offered. However, Heaney and Goldsmith (1999) found that there is a positive relationship between perceived benefit and information search for banking services. This is so since the consumers search for more information when they perceive the benefits that can be obtained from the offered services.…”
Section: Service Quality and Perceived Benefit With Smes Owners' Satimentioning
confidence: 94%
“…However, the deployed measure used in this study was adapted from the measures used by Heaney and Goldsmith (1999). Six items constitute the measure of the perceived benefits.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…Search Effort I searched for a lot of information. (Heaney & Goldsmith, 1999) I used many information cues.…”
Section: Product Involvementmentioning
confidence: 99%
“…Information search is influenced by numerous variables and researchers have studied a large number of them. Still, there have been few attempts to develop a model of external information search (Heaney & Goldsmith, 1999;Schmidt & Spreng, 1996). Schmidt and Spreng (1996) (Guo, 2001).…”
Section: Variables Influencing Information Searchmentioning
confidence: 99%